2022
DOI: 10.1007/s10113-022-01927-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dairy cattle production systems on sustaining soil organic carbon storage in grasslands of northern Spain

Abstract: Predicting the regional net greenhouse gas emissions (Net GHG) of grasslands is increasingly important, as these are one of the most globally widespread vegetation types, providing several ecosystem services. In this study, we assessed the regional soil organic carbon (SOC) change over a 30-year period (1981-2010), and the annual GHG balance for 405,000 ha of moist temperate Spanish grassland associated with dairy cow production. To do this we used the following: (i) an integrated modelling framework comprisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…However, excreta from other dairy cows and heifers are generally mixed with straw and other bedding and handled as solid manure (farmyard manure; FYM). Full details on the study area and dairy system characterisation can be found in Jebari et al (2022).…”
Section: Study Areamentioning
confidence: 99%
See 4 more Smart Citations
“…However, excreta from other dairy cows and heifers are generally mixed with straw and other bedding and handled as solid manure (farmyard manure; FYM). Full details on the study area and dairy system characterisation can be found in Jebari et al (2022).…”
Section: Study Areamentioning
confidence: 99%
“…For RothC initialisation, carbon pools were estimated according to Weihermüller et al (2013), based on the clay content values from Rodríguez Martín et al (2016), and SOC stocks for the year 2010 obtained from the simulation results from a previous paper by Jebari et al (2022). The initial IOM pool was set to match the equation proposed by Falloon et al (1998) (Eq.…”
Section: Soc Changementioning
confidence: 99%
See 3 more Smart Citations